Design of a Society of Automotive Engineers Regular Curved Retroreflector for Enhancing Optical Efficiency and Working Area - Lanh-Thanh Le; Hien-Thanh Le; Jetter Lee; Hsin-Yi Ma; Hsiao-Yi Lee (Crystals, 2018)
A highly efficient regular curved retroreflector is proposed to meet the requirements of the US Society of Automotive Engineers (SAE) regulations. It is demonstrated that 28% higher retroreflection efficiency and 33% more working area can be accomplished with the new designed retroreflector when compared with the commercial ones used in modern vehicles.